Kemampuan Peserta Didik dalam Menyelesaikan Soal Berbasis Higher Order Thinking Skills (HOTS) - Destrianti, Sindi; Septiana, Anisya; Harmi, Hendra; Anggraini, Safitri (ARITHMETIC: Academic Journal of Math, 2022)
The thinking ability of students can be improved by giving questions based on high-level abilities or Higher Order Thinking Skills (HOTS). The purpose of the study was to determine the ability of students to work on HOTS-based questions in class VIII MTs.S 1 Darussalam. This qualitative research was conducted at MTs.S 1 Darussalam. In this study, the data collection techniques used were observation, interviews, and documentation. The subjects of this study were 29 students from class VIII.D MTs.S 1 Darussalam with purposive sampling technique. Data analysis techniques in this study include data reduction, data presentation, and drawing conclusions. The results showed that there were 10% of students who got high HOTS scores, 66% of students got moderate HOTS scores, and 24% of students got low scores. Students who get high scores are those who can solve HOTS-based questions at levels C4, C5 and C6, for students who get moderate scores are those who are only able to work on HOTS questions at levels C4 and C5 only while students who get low scores can only do HOTS-based questions at the C4 level.